Resellers’ evaluation of TM consumer resellers training in meeting sales competency compliance requirements at Telekom Malaysia Berhad, Sarawak / Hawel Nyured... [et.al] - Nyured, Hawel; Nawawi, Nurerawady; Nawi, Rozita (2017)
The purpose of this study is to evaluate the TM Consumer Resellers Training by Telekom Malaysia Berhad in Sarawak in the context of sales competency compliance requirements. This study aims to evaluate the training at reaction, learning, behaviour and result level as per Kirkpatrick Model for training evaluation. Utilizing the survey approach, the study consisted of 32 Resellers and 13 Reseller Principals as respondents which is the whole population of Resellers and Reseller Principals in Sarawak. The results of the study indicated that the Resellers were highly satisfied with the training programme. They have gained more knowledge on sales competency compliance, reported better sales competency compliance behaviours and work results after attending the training programme. Therefore, recommendations include to continue the TM Consumer Resellers Training programme in Sarawak as well as ensuring that the learning environment and working environment arc conducive towards the Resellers for them to show more improvements in meeting sales competency compliance requirements from TM. Training evaluation also has to be planned and implemented completely following the implementation of such training programme. Sales competency compliance is important for TM for the purpose of maintaining a good reputation and service quality as Resellers represent their company and product when performing sales for TM.